Sodium danshensu modulates skeletal muscle fiber type formation and metabolism by inhibiting pyruvate kinase M1 - Zhang, Yunxia; Wu, Xiaoxiao; Li, Ruoqi; Sui, Mengru; Li, Guoyin; Fan, Shuhua; Yang, Mingsheng; Liu, Qiuping; Liu, Xiaomeng; Wu, Changjing; Li, Lili (Frontiers in Pharmacology, 2024)
Sodium Danshensu (SDSS) is extracted from Salvia miltiorrhiza and has many pharmacological effects. However, little is known about its effects on muscle fiber formation and metabolism. Here, we aimed to investigated the role and molecular mechanisms of SDSS in modulating the formation of skeletal muscle fiber. C2C12 cells were incubated in differentiation medium with or without SDSS for 4 days. C57BL/6 mice were orally administered SDSS by gavage once a day for 8 weeks. Grip strength, treadmill, muscle weight, western blotting, qPCR, immunofluorescence staining and H&E staining were performed. SDSS target proteins were searched through drug affinity responsive target stability (DARTS) and mass spectrometry analysis. Furthermore, molecular docking was carried out for Pyruvate kinase M1 (PKM1). The effect of PKM1 on myosin heavy chain (MyHCs) gene expression was verified by knockdown of PKM1 experiment. SDSS induced oxidative muscle fiber-related gene expression, and inhibited glycolytic fiber-related gene expression in C2C12 cells. Muscle mass, the percentage of slow oxidative fibers, succinic dehydrogenase activity, muscle endurance, glucose tolerance, and the expression of the MyHC1 and MyHC2a genes increased while MyHC2b expression, lactate dehydrogenase activity, and the percentage of glycolytic muscle fibers decreased in SDSStreated mice. Mechanistically, SDSS bound to the pyruvate kinase PKM1 and significantly repressed its activity. PKM1 inhibited MyHC1 and MyHC2a expression but promoted MyHC2b expression. SDSS also significantly attenuated the effects of PKM1 on muscle fiber-related gene expression in C2C12 cells. Our findings indicate that SDSS promotes muscle fiber transformation from the glycolytic type to the oxidative type by inhibiting PKM1 activity, which provide a new idea for treating muscle atrophy, muscle metabolism diseases and improving animal meat production.